(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In today’s dynamic digital landscape, mobile marketing and location-based services (LBS) have revolutionized customer-business interactions. Leveraging the capabilities of GPS-equipped mobile devices, businesses offer tailored experiences through personalized content and contextual notifications. This study explores the integrated impact of mobile marketing and location-based services on enhancing customer experiences.